2017
DOI: 10.1002/oby.21788
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of energy intake using just‐in‐time feedback from a wearable sensor system

Abstract: Objective This work explored the potential use of a wearable sensor system for providing just-in-time (JIT) feedback on the progression of a meal and tested its ability to reduce the total food mass intake. Methods Eighteen participants each consumed three meals in a lab while monitored by a wearable sensor system capable of accurately tracking chew counts. The baseline visit was used to establish the self-determined ingested mass and the associated chew counts. Real-time feedback on chew counts was provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Across the world, researchers from various disciplines work on exploiting these new opportunities to understand and ultimately improve behavioral health. New intervention designs, methods, and analysis strategies are being developed [ 61 - 64 ]. We expect that these novel research initiatives will be widely disseminated in the scientific literature, which will likely lead to an increase in the research output.…”
Section: Discussionmentioning
confidence: 99%
“…Across the world, researchers from various disciplines work on exploiting these new opportunities to understand and ultimately improve behavioral health. New intervention designs, methods, and analysis strategies are being developed [ 61 - 64 ]. We expect that these novel research initiatives will be widely disseminated in the scientific literature, which will likely lead to an increase in the research output.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is not yet a device for the automatic detection of eating that is practical for everyday use, despite the progress made in this area. Such devices, for example, require people to accurately position a sensor on the body with tape or require people to wear items like glasses or a hat to carry the functional parts [ 13 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study 41 showed that a faster rate of eating increased the mass and energy intake within a single meal. Similarly total chew counts per meal has been shown to have a relationship with total mass consumed in a single meal experiments 42 . We note that the method has proportional errors shown in Bland-Altman plots especially in the mass intake models using chew and sensor features.…”
Section: Discussionmentioning
confidence: 97%